Postharvest applications of clove essential oils on dry seeds stored under simulated warehouse conditions. Issue 1 (2nd January 2016) - Angioni, Alberto; Sarais, Giorgia; Melis, Marinella; Russo, Maria Teresa; Schirra, Mario; D'Aquino, Salvatore
Abstract: Clove essential oil was applied in postharvest trials on peanuts, beans, apricot kernels, and lentils stored in jute bags, and on wheat, maize, rice, and rape kept in silos, at ambient temperature (20°C). Eugenol, accounting for 85.6% of clove essential oil, has been used to assess clove essential oil residues after treatments in dry seeds. Two trials at different concentration and storage time were carried out. Immediately after treatment eugenol residues were under the instrumental limit of detection (LOD, 0.5 μg/Kg), except for wheat, peanuts, and rice (0.03, 0.10, 0.24, 0.23 mg/kg, respectively), and increased till a maximum after 2 weeks, except peanuts and apricot kernel which peaked after 30 days (12.69, and 0.47 mg/Kg, respectively). Sensory analysis showed that ventilation of the seeds allowed to decrease eugenol residue values under the flavor perception capacity of the in house panel (0.10 mg/kg), thus not affecting the organoleptic characteristics of the seeds.